2016
DOI: 10.1007/s10461-016-1379-9
|View full text |Cite|
|
Sign up to set email alerts
|

Awareness of Pre-exposure Prophylaxis for HIV, Willingness to Use It and Potential Barriers or Facilitators to Uptake Among Men Who Have Sex with Men in Spain

Abstract: There is a lack of data on pre-exposure prophylaxis (PrEP) effectiveness in Spain. We described the awareness of and willingness to use PrEP and examined potential barriers and facilitators to their use among men who have sex with men recruited either online or in voluntary HIV testing centers in Spain. Nearly a third of men (28.7 %) were aware of PrEP and 57.6 % said they would be willing to use it if available, 16.6 % saying they would be unwilling to use PrEP and 25.8 % not being sure. Men who had heard of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
4
19
6
Order By: Relevance
“…Previous studies showed mixed results for the influence of sampling strategies on findings regarding interest in PrEP. Beymer et al (2018), for example, reported higher interest in PrEP among visitors to an STI clinic compared to online participants, while Ferrer et al (2016) reported lower interest among visitors to an STI clinic compared to online participants. Overall, the pattern of results across studies is diverse, confirming our notion that recruitment strategies and sample characteristics can play a major role in explaining different findings.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed mixed results for the influence of sampling strategies on findings regarding interest in PrEP. Beymer et al (2018), for example, reported higher interest in PrEP among visitors to an STI clinic compared to online participants, while Ferrer et al (2016) reported lower interest among visitors to an STI clinic compared to online participants. Overall, the pattern of results across studies is diverse, confirming our notion that recruitment strategies and sample characteristics can play a major role in explaining different findings.…”
Section: Discussionmentioning
confidence: 97%
“…A 2012 study reported that only 28.2% of Australian MSM were willing to use PrEP [57]. More recently, in Europe, proportions of MSM willing to use PrEP have ranged from 47.8% to 54.3% in Scotland [58,59], 57.0% in Portugal [60] and 57.6 % in Spain [61]. Recent Canadian studies reported willingness to use PrEP of 55.0% [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating PrEP from PEP to potential adopters in LMIC would be important, at least initially. Studies from high-income settings such as Spain [61] have demonstrated the importance of awareness in determining willingness to use PrEP. Beyond just hearing about PrEP, the way in which PrEP information is provided to MSM, and how well they were able to understand it, could influence their levels of willingness to use it.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, our sample had a relatively good awareness of PrEP, having participated in a previous online PrEP survey, and therefore may not be similar to all MSMs in Malaysia. Awareness of PrEP is a critical determinant of willingness and acceptability to use it [ 31 ], and therefore public health implementation will require heavy focus on effective information dissemination and promotion of PrEP.…”
Section: Discussionmentioning
confidence: 99%